Moral politik santri : agama dan pembelaan kaum tertindas - Mulkhan, Abdul Munir, 1946- (Jakarta : Erlangga, 2003)
Sociology of Islam and political participation of Muslim scholars in Indonesia; collected articles.
Includes bibliographical references
Keywords: Islam sociology -- Indonesia; Islam -- 21st century; Scholars, Muslim -- Indonesia -- Political activity